Excitability properties of motor axons in adults with cerebral palsy - Klein, Cliff S.; Zhou, Ping; Marciniak, Christina (Frontiers in Human Neuroscience, 2015)
Cerebral Palsy (CP) is a permanent disorder caused by a lesion to the developing brain that significantly impairs motor function. The neurophysiological mechanisms underlying motor impairment are not well understood. Specifically, few have addressed whether motoneuron or peripheral axon properties are altered in CP, even though disruption of descending inputs to the spinal cord may cause them to change. In the present study, we have compared nerve excitability properties in seven adults with CP and fourteen healthy controls using threshold tracking techniques by stimulating the median nerve at the wrist and recording the compound muscle action potential (CMAP) over the abductor pollicis brevis. The excitability properties in the CP subjects were found to be abnormal. Early and late depolarizing and hyperpolarizing threshold electrotonus was significantly larger (i.e., fanning out), and resting current-threshold (I/V) slope was smaller, in CP compared to control. In addition resting threshold and rheobase tended to be larger in CP. According to a modeling analysis of the data, an increase in leakage current under or through the myelin sheath, i.e., the Barrett-Barrett conductance (GBB), combined with a slight hyperpolarization of the resting membrane potential, best explained the group differences in excitability properties. There was a trend for those with greater impairment in gross motor function to have more abnormal axon properties. The findings indicate plasticity of motor axon properties far removed from the site of the lesion. We suspect that this plasticity is caused by disruption of descending inputs to the motoneurons at an early age around the time of their injury.